PENGARUH SISTEM PENGENDALIAN INTERN TERHADAP KECURANGAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Fitri Jumi Rahayu; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2018)
This study aims to examine empirically the influence of government internal control system to the level of fraud on the financial statements of local government. The government's internal control system consists of several elements, that are control environment, risk assessment, control activities, information and communication, and monitoring. fraudulent financial statements are misstatements arising from fraud contained in financial reporting including misstatements or deliberate deletion of amounts in the financial statements to diceive the users of financial statements and misstatements resulting from undue treatment of assets.Data were collected using questionnaire survey. The questionnaires were delivered t0 72 employes of local government unit (SKPD) Semarang Regency specifically at financial/accounting departement. A total of 86 questionnaires 72 were returned and 64 can be proccesed. There are five hypotheses that were tested by using multiple regression analysis.The results of this study show that environment, risk assessment, control activities, information and communication and monitoring have significant negative effect on the level of fraud in the local government financial statements. This means that the better the government's internal control system (control environment, risk assessment, controlling activities, information and communication, monitoring) will lead to a decrease in the rate of fraud